A new species of Thinoscatella Mathis, 1979 from China (Diptera: Ephydridae), with an updated key to the world species - Zhang, Junhua; Yang, Ding (Zootaxa, 2005)
The genus Thinoscatella Mathis is recorded from China for the first time. A new species, Thinoscatella tibetensis sp. nov., is described. An updated key to the species of the genus from the world is presented.